Population uptake of antiretroviral treatment through primary care in rural South Africa - Cooke, Graham S.; Tanser, Frank; Bärnighausen, Till; Newell, Marie-Louise (BMC public health, 2010)
KwaZulu-Natal is the South African province worst affected by HIV and the focus of early modeling studies investigating strategies of antiretroviral treatment (ART) delivery. The reality of antiretroviral roll-out through primary care has differed from that anticipated and real world data are needed to inform the planning of further scaling up of services. We investigated the factors associated with uptake of antiretroviral treatment through a primary healthcare system in rural South Africa.
Gesehen am 31.08.2017